Respon Pertumbuhan Dan Produksi Tanaman Pakcoy (Brassica rapa L.) Terhadap Pemberian Pupuk Organik Kandang Ayam Dan Pupuk Organik Cair (Poc) Urin Sapi - Muhammad Yogie Ernanda; Asmah Indrawati; Siti Mardiana (Jurnal Ilmiah Pertanian ( JIPERTA), 2022)
Pakcoy crop (Brassica rapa L.) is included in the type of vegetable mustard which is quite economical. Today, pakcoy crop used by the community in various cuisines. This crop is quite easy to cultivate and only takes a short time of about 3 to 4 weeks. The purpose of this study to obtain data on the growth response and production of pakcoy crops on the application of organic fertilizer chicken manure and organic fertilizer cow urine liquid and can be a combination between the two treatments. This research was conducted at the Experimental Farm Faculty of Agriculture, University Medan Area, Kolam street No. 1 Medan Estate districts Percut Sei Tuan with a height of 20 meters above sea level (asl) in the months of October to December 2016. This research has been done by using factorial randomized block design consisting of two factor. The first factor treatment which tested is organic fertilizer chicken manure is A0= Control (without organic fertilizer chicken manure); A1= fertilizer chicken manure 1 kg/m2; A2= fertilizer chicken manure 2 kg/m2 dan A3= fertilizer chicken manure 3 kg/m2. The second factor tested is POC concentration of cow urine is : S0= Control (without cow urine); S1= 30 ml urin sapi / L of water ; S2= 60 ml urin sapi / L of water dan S3= 90 ml urin sapi / L of water. The results showed that organic fertilizer chicken manure treatment had significant effect on the parameters of plant height from age 2 MST to 4 MSTÂ  wet weight per sample. the best treatment is A3 (3kg/plot).